A light-controlled multi-step drug release nanosystem targeting tumor hypoxia for synergistic cancer therapy. Issue 35 (10th August 2021) - Zhang, Bin; Xu, Zichen; Zhou, Wen; Liu, Zhikun; Zhao, Jian; Gou, Shaohua
Abstract : A photo-responsive ruthenium complex-derived micelle (CC5-RuCa) loaded with CC5 was prepared for light and tumor microenvironment-controlled multistage drug-release. Abstract : Hypoxia is a major obstacle for cancer therapy due to its association with cell proliferation, tumor distant metastasis, and treatment resistance. In this study, a hypoxia-activated bifunctional prodrug (CC5) was designed, synthesized and encapsulated by a photo-responsive ruthenium complex-derived polymer to yield a light-controlled multi-step drug release system (CC5-RuCa) for synergistic therapy against tumor hypoxia. Under NIR irradiation, CC5-RuCa not only generated ROS to kill the cancer cells in the exterior of the tumor but also released the prodrug CC5 with enhanced intratumoral penetration in the severe hypoxia region inside the tumor tissue. In vivo studies on MDA-MB-231 xenograft models revealed that CC5-RuCa with preferential accumulation in the tumor exhibited highly efficient tumor regression through the synergistic effect of photodynamic therapy and hypoxia-activated chemotherapy.